Indicators of temperature anomalies of regional climate - Шевченко, Ольга Григорівна; Сніжко, Сергій Іванович; Олійник, Ростислав Васильович; Костирко, Іван (Київський національний університет імені Тараса Шевченка, 2018)
Climatic indices are usually created for a particular group or sector of influence, and because of their complexity they cannot be universal and apply for more than one region. In addition, a methodology is needed that would allow studying of changes in the index over a long period of time using climatological data (both models and observations). That is why there are many metrics (or indexes) that try to provide quantitative information about the periods of extreme heat. Since there are many different climatic regimes in one region, it is necessary to focus on observations of extreme temperatures over the research territory. Thus, the anomalies of the air temperature regime that were recorded at 18 meteorological stations of Ukraine during the reference period of 1981-2010 were considered in this study. To assess the effects of hot events (especially heat waves) for a selected region, it is important to know how the climate indicator is evaluated. To assess the effects of hot events, in particular, heat waves, for a particular region, it is important to know how the climate indicator is evaluated this event because there is a certain risk that the inadequate index distorts the climatological information, which in turn leads to ineffective planning of adaptation and mitigation. Therefore, it is necessary to use the index of a climatic event, which could be easily calculated based on the regional climatic data and which could provide comprehensive information that characterizes the heat event which is observed. The latest studies show, the HWMI index is considered an alternative index of temperature regime. HWMI indices were calculated based on the analysis of the maximum daily air temperature series for the calendar year. This was achieved due to the temperature thresholds established on a single metric, which is the most important for which the heat waves were identified and estimated. The annual thresholds of maximum daily air temperature for different reference periods (1961-1990 and 1981-2010) were investigated. It was found out, there is the difference in the threshold values of maximum air temperature during the year for the indicated reference periods only in winter (January-February) and in summer (July-August) and did not exceed 3°С. The field of maximum temperature thresholds for the reference period, which focuses on the south-east of the country, is established. The spatial variability of temperature thresholds along the zonal and meridional sections was studied, which allowed optimizing the grid for the construction of the regional field of threshold extreme temperatures.

Щоб оцінити вплив, зокрема хвиль тепла, для конкретного регіону, важливо знати, як той чи інший індикатор оцінює дану подію, оскільки використання однобічних індексів викривляє кліматологічну інформації, що в свою чергу призводить до неефективного планування адаптації та пом’якшення наслідків. Отже, необхідно використовувати такий індекс кліматичної події, який легко розраховується виходячи з кліматичних даних відповідного регіону і може надавати інформацію, що адекватно відображає досліджувану подію. Як показують останні дослідження, на сьогоднішній день альтернативним індексом температурного режиму вважається індекс HWMI. На основі аналізу рядів максимальних добових температур повітря для 18 метеорологічних станцій України протягом референтного періоду 1981-2010 рр. за календарне літо, розраховані індекси HWMI. Це вдалося реалізувати завдяки встановленим за єдиною метрикою температурним порогам, саме відносно яких ідентифікувалися і оцінювалися хвилі тепла. Побудовано поле температурних порогів для досліджуваного референтного періоду та обґрунтовано його територіальний розподіл.
Індикатори температурних аномалій регіонального клімату
ШевченкоО.Г., Сніжко С.І. Хвилі тепла та основні методологічні проблеми, що виникають при їх дослідженні // Український гідрометеорологічний журнал. – 2012. − № 10. – С. 57-63. AlexanderV. et al. Global observed changes in daily climate extremes of temperature . Journal of Geophysical Research : Atmospheres v.111, p.1-22 (2006). Avila A.J., Pitman M.G., Donat L.V., Alexander G. Abramowitz. Climate model simulated changes in temperature extremes due to land cover change . Journal of Geophysical Research v.117, p.1-19 (2012). Barriopedro David, Fischer Erich M., Luterbacher Jürg, Trigo Ricardo M., García-Herrera Ricardo. The Hot Summer of 2010 : Redrawing the Temperature Record Map of Europe. Scienc 332, 220-224 (2011). Battisti, D.S,. Naylor, R.L. Historical Warnings of Future Food Insecurity with Unprecedented Seasonal Heat. Science, 323, 240-244, (2009). Coumou Dim, Alexander Robinson. Historic and future increase in the global land area affected by monthly heat extremes. Environmental Research Letters, v. 8, № 3, 1-3, (2013). Fischer E.and Schär C. Consistent geographical patterns of changes in high-impact European heatwaves, Nature Geoscience 3, 398-403 (2010). Fischer et al. Climate change effects on Chikungunya transmission in Europe . International Journal of Health Geographics. V.12: 51 (2013). García-Herreraetal R., Diaz J., Trigo R. M., Luterbacher J., Fisher E.M. A Review of the European Summer Heat Wave of 2003. Critical Reviews in Environmental Science and Technology v.40. p.267-306 (2010). Gerald A. Meehl, Claudia Tebaldi. More Intense, More Frequent, and Longer Lasting Heat Waves in the 21st Century . Science V. 305, p. 994-997 (2004). Perkins, S. E., L. V. Alexander. On the measurement of heat waves, J. Clim.,26, p.4500–4517(2012). Russo et al., Magnitude of extreme heat waves in present climate and their projection in a warming world . Journal of Geophysical Research: Atmospheres v.119, p.1-13. (2014). Schär C, Vidale PL, Lüthi D, Frei C, Häberli C, Liniger MA, Appenzeller C. The role of increasing temperature variability in European summer heatwaves . Nature 427, 332-336 (2004). Sillmann J. Kharin V.V. Zhang X. Zwiers F. W. Bronaugh D. Climate extremes indices in the CMIP5 multimodel ensemble : Part 1. Model evaluation in the present climate . Journal of Geophysical Research v.118, p.1716-1733 (2013). Williams M., Eggieston S. Using indicators to explain our changing climate to policymakers and the public / Bulletin WMO nº: Vol 66 (2) – 201.
Keywords: температурні пороги; температурні аномалії; хвилі тепла; хвилі підкачки хвиль тепла; індекс магнітуди хвилі тепла; temperature thresholds; temperature anomalies; waves of heat; waves of heat wave propagation; index of heat wave magnitude